2007
DOI: 10.1038/sj.leu.2404603
|View full text |Cite
|
Sign up to set email alerts
|

Why and how to quantify minimal residual disease in acute lymphoblastic leukemia?

Abstract: Several studies have demonstrated that monitoring of minimal residual disease (MRD) in childhood and adult acute lymphoblastic leukemia (ALL) significantly correlates with clinical outcome. MRD detection is particularly useful for evaluation of early treatment response and consequently for improved front-line therapy stratification. MRD information is also significant for children undergoing allogeneic hematopoietic stem cell transplantation and those with relapsed ALL. Currently, three highly specific and sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(59 citation statements)
references
References 46 publications
1
53
0
2
Order By: Relevance
“…Current MRD assays are based on polymerase chain reaction amplification of antigen-receptor genes and detection of abnormal immunophenotypes by multiparametric flow cytometry. 7,16,17 Multiparametric flow cytometry-based assays are rapid, readily available and provide accurate MRD quantification while simultaneously yielding information on normal hematopoietic status. 9 Multiparametric flow cytometry and polymerase chain reaction amplification of the genes encoding immunoglobulin and T-cell receptor proteins estimate similar levels of MRD in most remission samples obtained from children with ALL, 8,[18][19][20] when the level of MRD is 0.01% or greater.…”
Section: Discussionmentioning
confidence: 99%
“…Current MRD assays are based on polymerase chain reaction amplification of antigen-receptor genes and detection of abnormal immunophenotypes by multiparametric flow cytometry. 7,16,17 Multiparametric flow cytometry-based assays are rapid, readily available and provide accurate MRD quantification while simultaneously yielding information on normal hematopoietic status. 9 Multiparametric flow cytometry and polymerase chain reaction amplification of the genes encoding immunoglobulin and T-cell receptor proteins estimate similar levels of MRD in most remission samples obtained from children with ALL, 8,[18][19][20] when the level of MRD is 0.01% or greater.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, with the exception of graft-versus-leukemia (GVL) effect, there are not many treatment options available today to eradicate residual malignant cells. However, GVL effect is mediated by GVHD, a potentially dangerous and usually mortal condition often developed by patients following HSCT [22] . Therefore, it is necessary to develop new strategies to treat patients post-HSCT.…”
Section: Tca Synergized the Cytotoxicity Of Cik Cells To K562 Cellsmentioning
confidence: 99%
“…[20][21][22][23] In Ph-positive (Ph þ ) ALL cases, quantitative detection of the BCR/ABL fusion transcript provides an alternative option for follow-up. MRD monitoring based on fusion transcript detection possesses some disadvantages, 24 but the substantial advantage of this method is the opportunity to use a universal system for fusion transcript identification and monitoring, which makes this method relatively easier, faster and cheaper than the Ig/TCR approach. We have previously shown that in TEL/AML1-positive childhood ALL, fusion transcript-based MRD monitoring is clinically relevant and closely correlates with the Ig/TCR approach.…”
Section: Introductionmentioning
confidence: 99%